Exposure characteristics and cumulative risk assessment of bisphenol A and its substitutes: the Taiwan environmental survey for toxicants 2013 - Lin, Yu-Jung; Chen, Hsin-Chang; Chang, Jung-Wei; Huang, Han-Bin; Chang, Wan-Ting; Huang, Po-Chin (Frontiers in Public Health, 2024)
Introduction Ever since the use of bisphenol A (BPA) has been restricted, concerns have been raised regarding the use of its substitutes, such as bisphenol S (BPS) and bisphenol F (BPF). Meanwhile, the EU European Food Safety Authority (EFSA) issued the new tolerable daily intake (TDI) after the latest re-risk assessment for BPA, which enforced the need for cumulative risk assessment in the population. This study was conducted to identify BPA and its substitute’s exposure characteristics of the general Taiwanese population and estimate the cumulative risk of bisphenol exposure. Methods Urine samples (N = 366 [adult, 271; minor, 95]) were collected from individuals who participated in the Taiwan Environmental Survey for Toxicants 2013. The samples were analyzed for BPA, BPS, and BPF through ultraperformance liquid chromatography–tandem mass spectrometry. Daily intake (DI) levels were calculated for each bisphenol. Hazard quotients (HQs) were calculated with the consideration of tolerable DI and a reference dose. Additionally, hazard index (HI; sum of HQs for each bisphenol) values were calculated. Results Our study found that the median level of BPA was significantly higher in adults (9.63 μg/g creatinine) than in minors (6.63 μg/g creatinine) (p < 0.001). The DI of BPS was higher in female (0.69 ng/kg/day) than in male (0.49 ng/kg/day); however, the DIs of BPF and BPS were higher in boys (1.15 and 0.26 ng/kg/day, respectively) than in girls (0.57 and 0.20 ng/kg/day, respectively). Most HI values exceeded 1 (99% of the participants) after EFSA re-establish the TDI of BPA. Discussion Our study revealed that the exposure profiles and risk of BPA and its substitute in Taiwanese varied by age and sex. Additionally, the exposure risk of BPA was deemed unacceptable in Taiwan according to new EFSA regulations, and food contamination could be the possible source of exposure. We suggest that the risk of exposure to BPA and its substitutes in most human biomonitoring studies should be reassessed based on new scientific evidence.